IMPORT SUBSTITUTION IN THE RUSSIAN TOURISM INDUSTRY - N. M. Mukhetdinova (Финансы: теория и практика)
The intensive import substitution in the economy caused by the anti-Russian US and EU sanctions also involves the Russian tourism industry. The paper analyzes internal and external factors leading to the import substitution expansion in the Russian economy. The common and different features of the import substitution in the production of goods and services are considered. The organizational mechanisms for import substitution of a tourism productbased on close cooperation between the state and business are identified. The forms of the public-private partnershipin this area and the progress of the federal target program “The Development of the Domestic and Inbound Tourism in the Russian Federation (2011-2018)” are discussed. The ways of increasing the role of the Russian regions in the development of domestic and inbound tourism and the structural transformation of the industry are discussed. The paper makes it plain that the success of the import substitution largely depends on how effective is the cooperation between the state and business in the framework of the public-private partnership. It is concluded that the import substitution policy can transform the Russian tourism industry into a competitive sector of the Russian economy, an economic growth driver, capable of bringing budget revenues and reducing dependence on raw materials.